THE EFFECT OF THE STEM APPROACH THROUGH DIFFERENTIATIONAL LEARNING ON EMOTIONAL ABILITIES OF CHILDREN AGED 5–6 YEARS QUASI-EXPERIMENTAL STUDY - Ningsih, Sulastya; MM Sodik, Nurul Aini; M Sumirat, Elva; Indrawati, Ni Putu Vivin (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to analyze the influence of implementing a STEM approach through learning differentiation on children's emotional abilities aged 5–6 years. Research uses a quantitative, quasi-experimental, nonequivalent control-group design. Subjects, 20 children in total, were divided into experimental and control groups. Data collected through observation and the structured use of the instrument to assess emotional ability, including four aspects: introduction to emotions, self-control, empathy, and expression of positive emotions. Data analysis was carried out using paired t-test, independent t-test, and gain score analysis. Research results show that both groups demonstrate significant emotional ability (p < 0.05), and the improvement in the experimental group is greater than in the control group. The average posttest score in the experimental group was 72.3, while the average score in the control group was 55.0. The effect size value (Cohen's d) of 4.91 indicates that the intervention has a very strong influence. Findings show that learning STEM-based skills through a differentiation approach is effective in developing children's abilities at an early age. Approach: This provides experience, challenging, collaborative, and adaptive learning, thereby supporting optimal development of regulation, emotions, and empathy in children.